2001
DOI: 10.1002/acp.724
|View full text |Cite
|
Sign up to set email alerts
|

Indexing space and time in film understanding

Abstract: We investigated the extent to which understanders monitor shifts in time and space during ®lm comprehension. Participants viewed a feature-length ®lm and identi®ed those points in the ®lm in which they perceived a change in situation. We performed an a priori analysis of the ®lms to identify the shifts in time, the movement of characters, and region. The relationship between the theoretical analysis of the ®lms and the participants judgements of situational change was assessed. The results provide support for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
191
1
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(219 citation statements)
references
References 18 publications
21
191
1
6
Order By: Relevance
“…Larger physical changes have been studied using commercial cinema as a stimulus, in which the locations and temporal setting of characters can change from shot to shot. In one study, such changes were found to predict where viewers segmented Hollywood movies [7]. Conceptual changes that are correlated with event boundaries include changes in goals of actors, in causal relations and in interactions amongst characters [8,9].…”
Section: Segmentation Tasksmentioning
confidence: 99%
“…Larger physical changes have been studied using commercial cinema as a stimulus, in which the locations and temporal setting of characters can change from shot to shot. In one study, such changes were found to predict where viewers segmented Hollywood movies [7]. Conceptual changes that are correlated with event boundaries include changes in goals of actors, in causal relations and in interactions amongst characters [8,9].…”
Section: Segmentation Tasksmentioning
confidence: 99%
“…There is evidence, however, that film and reading comprehension share similar cognitive processes (Magliano, Loschky, Clinton, & Larson, 2013;Magliano, Miller, & Zwaan, 2001) so a degree of extrapolation from reading to film is appropriate. Comprehension, in general, involves hierarchical cognitive process where information is encoded at a shallow level and proceeds through the cognitive system resulting in a mental representation or a situation model (Zwaan & Radvansky, 1998).…”
mentioning
confidence: 99%
“…context of film (Baggett, 1979;Magliano, Dijkstra, & Zwaan, 1996;Magliano, Miller, & Zwaan, 2001;Schwan, Garsoffky, & Hesse, 2000;Tan, 1996), as compared with that for narrative text. Theories and empirical findings derived from research on narrative texts should generalize to narrative film ).…”
mentioning
confidence: 99%